Implementasi Sistem Penilaian Kinerja Berbasis Digital pada Divisi Digital Marketing PT Pos Indonesia (Persero) Regional V Surabaya - Hani, Alyyah Rahma Putri; Kustini, Kustini (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This community service activity was conducted in the Digital Marketing Division of PT Pos Indonesia (Persero) Regional V Surabaya, aiming to support the implementation of a digital performance appraisal system through the Ihsan Pos and Jobman applications. The background of this activity lies in the ongoing challenges such as data entry difficulties, delays in validation, and limited staff understanding of the Objective and Key Results (OKR) framework and the AKHLAK values, which serve as the foundation for performance evaluation in the company.The implementation used a descriptive qualitative approach, involving participatory observation, interviews with relevant staff, and documentation of the implementation process. Participating students were actively involved in inputting OKR data, synchronizing job descriptions, and assisting with final validation by direct supervisors.The results showed an improvement in the efficiency of the performance appraisal process, with data input time reduced from three days to one working day, and data completeness increasing from 72% to 96%. Staff understanding of the system also improved, as evidenced by 80% of staff being able to operate the application independently after mentoring.In conclusion, this community service activity had a positive impact on the speed and accuracy of the performance appraisal process. However, further training is needed to ensure all employees can formulate OKRs effectively according to SMART principles.